- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,812

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,812

- Mar 31, 2013

- 1,334

So $(\sqrt x)^3 + 9 x + 9 (\sqrt x) + 9 = 0$

Or $(\sqrt x)(x + 9) = - 9(x+1)$

Or squaring $x(x+9)^2 = 81(x+1)^2$

Or $x(x^2 + 18 x + 81) = 81 x^2 + 162x + 81$

Or $x^3 - 63x^2 - 81 x - 81 = 0$

This is the required equation

Does the above mean that if a,b,c are the 3 roots of the above polynomial then the the roots of the new polynomial must be $a^2 ,b^2 , c^2$ ??

So $(\sqrt x)^3 + 9 x + 9 (\sqrt x) + 9 = 0$

Or $(\sqrt x)(x + 9) = - 9(x+1)$

Or squaring $x(x+9)^2 = 81(x+1)^2$

Or $x(x^2 + 18 x + 81) = 81 x^2 + 162x + 81$

Or $x^3 - 63x^2 - 81 x - 81 = 0$

This is the required equation

- Mar 31, 2013

- 1,334

as $\sqrt{x}$ is positive by definition so my line should be $\pm \sqrt{x}$ and the we get the same result because of squaring

Let a,b,c be the roots of P(x) = $x^3+9x^2+9x+9$

And $a^2, b^2 ,c^2 $ the roots of P(y)= $y^3+Ay^2+By+C$

From the polynomial properties we have:

P(x) = $x^3+9x^2+9x+9$=(x-a)(x-b)(x-c) $\Rightarrow$...............

.a+b+c=-9................... (1)

ab+ac+bc=9 ................(2)

abc=-9 ................................(3)

And also P(y)= $y^3+Ay^2+By+C$=$(y-a^2)(y-b^2)(y-c^2)\Rightarrow $

$a^2+b^2+c^2=-A$.................................................(4)

$a^2b^2 +a^2c^2+b^2c^2=B$...............................(5)

$ a^2b^2c^2=-C$.............................................................(6)

From(3) we have:$a^2b^2c^2=81$ hence

C=-81.....................................................................................(7)

From (1) and squaring we get :

$(a+b+c)^2=81\Rightarrow a^2+b^2+c^2= 81-2(ab+ac+bc) $ and using (2) we get :

$a^2+b^2+c^2= 63$ and hence :

A= -63.................................................................................(8)

From (2) and squaring we get:

$(ab+ac+bc)^2=81\Rightarrow a^2b^2+a^2c^2+b^2c^2+2(a^2bc+ab^2c+abc^2)=81\Rightarrow

a^2b^2+a^2c^2+b^2c^2+2(a(abc)+b(abc)+c(abc))=81$ and using (3) we have:

$a^2b^2+a^2c^2+b^2c^2 =81-2(-9a-9b-9c)=81+18(a+b+c)$ and using (1) we have:

$a^2b^2+a^2c^2+b^2c^2=81+18(-9)=-81$ hence:

B=-81.................................................................................(9)

And P(y)= $y^3+Ay^2+By+C =y^3-63y^2-81y-81$ by using (7),(8),(9)

Last edited by a moderator: